2020
DOI: 10.3390/cancers12123679
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Encapsulated Bacillus Calmette–Guérin Cell Wall Skeleton Enhances Antitumor Efficiency for Bladder Cancer In Vitro and In Vivo via Induction of AMP-Activated Protein Kinase

Abstract: The Mycobacterium Bacillus Calmette-Guérin cell wall skeleton (BCG-CWS), the main immune active center of BCG, is a potent candidate non-infectious immunotherapeutic drug and an alternative to live BCG for use against urothelial carcinoma. However, its application in anticancer therapy is limited, as BCG-CWS tends to aggregate in both aqueous and non-aqueous solvents. To improve the internalization of BCG-CWS into bladder cancer cells without aggregation, BCG-CWS was nanoparticulated at a 180 nm size in methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…It determines that more DOX in EF-DOX-Lips is delivered into cells after 1 h, especially after MWA is added, since MWA-induced heat also enhances permeability for drug delivery akin to other heat-enhanced permeability. 40,41 After 3 h, LCSM images and FCM results show that MWA triggers an abundant DOX release and the accumulation from EF-DOX-Lips in nuclei (Figures 4f,g and S3a) and subsequently induces the highest cytotoxicity (91.9% vs 60−75%) (Figures 4h,i and S3b). A prolonged incubation time induces more deaths (Figure 4j).…”
Section: Resultsmentioning
confidence: 99%
“…It determines that more DOX in EF-DOX-Lips is delivered into cells after 1 h, especially after MWA is added, since MWA-induced heat also enhances permeability for drug delivery akin to other heat-enhanced permeability. 40,41 After 3 h, LCSM images and FCM results show that MWA triggers an abundant DOX release and the accumulation from EF-DOX-Lips in nuclei (Figures 4f,g and S3a) and subsequently induces the highest cytotoxicity (91.9% vs 60−75%) (Figures 4h,i and S3b). A prolonged incubation time induces more deaths (Figure 4j).…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, studies on increasing the invasion of BCG were conducted. Drug delivery systems such as nanocarriers or liposomes could promote endocytosis and the antitumor effects of BCG [ 32 ]. In the case of these upgraded tools, low-dose BCG can be used to reduce adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, BCG-CWS nanoparticles were encapsulated in liposomes in order to reduce the side effects of BCG treatment. As a result of this study, increased antitumor activity was also shown with the induction of autophagy and ROS production [ 122 ].…”
Section: Nano-immunotherapy Applications In Cancer Treatmentmentioning
confidence: 98%